Evaluating the Potential and Challenges of Utilising Computational Simulation to Design Safety Management and Culture Interventions. - Goh Y.M. (2018)
CIB W099 International Conference on Achieving Sustainable Construction Health and SafetyIngvar Kamprad Design Centre (IKDC), Lund, Sweden